2022
DOI: 10.3390/antibiotics11091213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing Reveals Environmental Dispersion of Antibiotic-Resistant Enterococci under Anthropogenic Pressure

Abstract: As a consequence of global demographic challenges, both the artificial and the natural environment are increasingly impacted by contaminants of emerging concern, such as bacterial pathogens and their antibiotic resistance genes (ARGs). The aim of this study was to determine the extent to which anthropogenic contamination contributes to the spread of antibiotic resistant enterococci in aquatic compartments and to explore genetic relationships among Enterococcus strains. Antimicrobial susceptibility testing (amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…In contrast to the current study, Farkas et al [ 92 ] observed that E. faecium isolates from aquatic matrices exhibited the same or similar ERIC-PCR fingerprints to that of hospital-derived variants as they clustered within the same clade. This is significant as E. faecium has been associated with HA infections, however the bacteria are rarely observed amongst healthy individuals [ 92 ]. The results of the current study are however, comparable to observations made by Serrano et al [ 93 ], as the P. aeruginosa REP-PCR demonstrated that a wide genetic diversity was observed across the P. aeruginosa ( n = 16) clinical and environmental isolates.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the current study, Farkas et al [ 92 ] observed that E. faecium isolates from aquatic matrices exhibited the same or similar ERIC-PCR fingerprints to that of hospital-derived variants as they clustered within the same clade. This is significant as E. faecium has been associated with HA infections, however the bacteria are rarely observed amongst healthy individuals [ 92 ]. The results of the current study are however, comparable to observations made by Serrano et al [ 93 ], as the P. aeruginosa REP-PCR demonstrated that a wide genetic diversity was observed across the P. aeruginosa ( n = 16) clinical and environmental isolates.…”
Section: Discussioncontrasting
confidence: 99%
“…While limited literature is available on the extensive epidemiological survey of E. faecium , K. pneumoniae , and P. aeruginosa in environmental reservoirs, REP-PCR has previously been implemented in the medical, agricultural and food industries for the identification of contamination sources, cross-transmission routes, and the recognition of virulent strains [ 91 , 92 ]. For example, Farkas et al [ 92 ] investigated the extent to which anthropogenic contamination contributes to the spread of antibiotic resistant enterococci in aquatic environments and additionally explored the genetic relationships (REP-PCR with ERIC primers) amongst Enterococcus strains (i.e., E. avium, E. faecalis and E. faecium ). In contrast to the current study, Farkas et al [ 92 ] observed that E. faecium isolates from aquatic matrices exhibited the same or similar ERIC-PCR fingerprints to that of hospital-derived variants as they clustered within the same clade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococcus species have frequently been described as carriers of antibiotic resistance across the One Health continuum. Hospital effluents, untreated sewage, and raw manure have been identified as the main hotspots for antibiotic-resistant enterococci and as sources for their environmental spread [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enterococci are Gram-positive facultative anaerobic cocci that constitute normal commensal microbiota of the human gastrointestinal tract ( Attallah et al, 2022 ). In recent years, enterococci have become one of the leading causes of hospital-acquired infections and are common pathogens in various wound and surgical site infections ( Farkas et al, 2022 ). The isolation rate of clinical strains Enterococcus is high among which Enterococcus faecalis ( E. faecalis ) and Enterococcus faecium ( E. faecium ) were the most prominent ( Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%